The pathological changes of the digestive system for Anas platyrhychos in Baghdad and Kut in Iraq which infectel with platyhelminthes and nematodes - Baghdad Science Journal (مجلة بغداد للعلوم)
A total of 247 Mallard ( Anas platyrhynchos platyrhynchos L.) from Baghdad and Kut were examined for the Cestodes Diorchis stefanskii Sobolevicanthes gracilis; Hymenolepis mastigopraditae and the Nematode Amidostomum acutum in the first time in Iraq . Among these , 151 birds were found infected by these helminthes It has been found small nodules on the external surface of the intestine , Ulceration of mucosa inflammatory infiltrate , Oedemats changes and hyperplasia in the section of infected intestine were noticed.